Immobilized Forms of the Ophiostoma piceae Lipase for Green Synthesis of Biodiesel. Comparison with Eversa Transform 2.0 and Cal A - María Molina-Gutiérrez; Lorena Alcaraz; Félix A. López; Leonor Rodríguez-Sánchez; María Jesús Martínez; Alicia Prieto (Journal of Fungi, 2021)
In this work, we analyzed the suitability of a versatile recombinant lipase, secreted by Ophiostoma piceae (OPEr) and produced in Pichia pastoris, as a catalyst of the synthesis of biodiesel. The enzyme was immobilized by five covalent procedures and by hydrophobicity on functionalized nanoparticles of magnetite or of a novel Zn/Mn oxide named G1. Then, they were tested for green production of biodiesel by solventless enzymatic transesterification of discarded cooking oil and methanol (1:4) at 25 °C. The results were compared with those shown by free OPEr and the commercial lipases Eversa® and Cal A®. Several preparations with immobilized OPEr produced high synthesis yields (>90% transesterification), comparable to those obtained with Eversa®, the commercial enzyme designed for this application. Three of the biocatalysts maintained their catalytic efficiency for nine cycles. The process catalyzed by AMNP-CH-OPEr was scaled from 500 µL to 25 mL (50 times), improving its efficiency.